The Decadence Of Exemplary Values Of Islamic Education Leaders: A Critical Study From The Perspective Of Management And Qur'anic Ethics - Nikmatul Khoiriah; Ahmad Thib Raya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The decline of exemplary leadership represents a fundamental challenge in contemporary Islamic education, where leadership is increasingly reduced to administrative functions rather than serving as a moral and spiritual role model. This study aims to critically analyze the decadence of exemplary leadership in Islamic educational institutions from the perspective of Islamic educational management grounded in Qur’anic ethics. Employing a qualitative library research approach, this study applies thematic tafsir analysis of Qur’anic verses and prophetic traditions related to leadership, trust (amanah), justice, honesty, and ihsan, and integrates them with contemporary Islamic educational management literature. The findings indicate that the weak internalization of Qur’anic values in leadership practices results in crises of integrity, moral inconsistency, and value dissonance, which negatively affect organizational culture, institutional trust, and the normative goals of Islamic education. This study emphasizes that exemplary leadership constitutes the core legitimacy of leadership in Islamic education and cannot be replaced by managerial competence alone, and it proposes a conceptual framework for restoring Islamic educational leadership through the integration of Qur’anic ethics and modern management principles.